2014
DOI: 10.1007/s00705-014-2257-2
|View full text |Cite
|
Sign up to set email alerts
|

Oysters as hot spots for mimivirus isolation

Abstract: Viruses are ubiquitous organisms, but their role in the ecosystem and their prevalence are still poorly understood. Mimiviruses are extremely complex and large DNA viruses. Although metagenomic studies have suggested that members of the family Mimiviridae are abundant in oceans, there is a lack of information about the association of mimiviruses with marine organisms. In this work, we demonstrate by molecular and virological methods that oysters are excellent sources for mimiviruses isolation. Our data not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Amoeba, however, does not have a cell wall, consistent with the observation that bald Mimivirus, which does not contain R135, infects amoeba as does the wild-type fibered virus. The possibility that Mimivirus might infect alternative hosts was also implied recently by the discovery that Mimiviruses were found to be abundant in oysters (Andrade et al, 2014). …”
Section: Resultsmentioning
confidence: 95%
“…Amoeba, however, does not have a cell wall, consistent with the observation that bald Mimivirus, which does not contain R135, infects amoeba as does the wild-type fibered virus. The possibility that Mimivirus might infect alternative hosts was also implied recently by the discovery that Mimiviruses were found to be abundant in oysters (Andrade et al, 2014). …”
Section: Resultsmentioning
confidence: 95%
“…Independently of the sugar that first interacted with the mimivirus particles, attachment to any sugar prevents interaction of the viral particles with other molecules, because the fibrils are completely saturated by the carbohydrate. Mimiviruses have already been isolated from distinct animals, such as the Shan virus and the LBA111 virus from humans (25,26), Hirudovirus from the invertebrate Hirudo medicinalis (27), and some viruses that have not yet been characterized from oysters (28). Furthermore, it has already been demonstrated that mimiviruses circulate among nonhuman mammals (29).…”
Section: Discussionmentioning
confidence: 99%
“…Hewson et al (2014) identified a novel Forbes sea star ( Asterias forbes ) virus (AFSSV) as the causative agent of a wasting disease condition linked to high mortality in the Forbes sea stars. On the other hand, Andrade et al (2015) showed that oysters are the hotspots for Mimivirus isolations which are the largest viruses found in the world with >1,100,000 bp length. Overall, these findings show that viral metagenomics analysis is a powerful tool able to identify novel pathogenic viruses infecting different aquatic organisms.…”
Section: Discovery Of New Viruses Using Viral Metagenomicsmentioning
confidence: 99%